Growth and yield of an eucalyptus subtropical plantation in a Northeastern Mexico degraded land soil - Foroughbakhch Pournavab, Rahim; Carrillo Parra, Artemio; Hernández Piñero, Jorge Luis; Guzmán Lucio, Marco Antonio (Instituto de Ecología, A.C., 2017)
Over the past three decades, woody species potentially useful for reforestation, fuelwood, coal and timber production have been over-exploited along the Gulf of Mexico, which has led to a gradual decline in the plant population and the progressive degradation of the environment. The present research evaluated the establishment, growth, and production of fuelwood from a plantation of five eucalyptus species planted in randomly arranged plots on a cleared clayey loam alkali soil in a semi-arid region of northeastern Mexico for a 20 year period. Eucalyptus camaldulensis, E. tereticornis and E. microtheca showed the highest average height growth rate (1.07 m year-1, 0.93 m year-1 and 0.85 m year-1, respectively). E. camaldulensis showed the highest volume values at 20 years (58.55 m3 ha-1), followed by E. tereticornis (54.15 m3 ha-1) and E. microtheca (51.91 m3 ha-1). E. sideroxylun and E. crebra yielded the lowest tree volumes (35.12 m3 ha-1 and 30.45 m3 ha-1, respectively). The results have shown that the adaptability of eucalyptus species to the climate of the subtropical regions allows their use in combination with the native vegetation to colonize degraded areas offering services in timber and non-timber products to the local population. In addition, the production of exotic trees with large trunk diameter with few side branches may increase the volume of the wood exploited and the income to the owner of the land and, thus, reduce the pressure on the native species.